2017
DOI: 10.1080/07347332.2017.1292573
|View full text |Cite
|
Sign up to set email alerts
|

Parental spirituality in life-threatening pediatric cancer

Abstract: This study addressed parental spirituality in the context of pediatric cancer with a poor prognosis. Drawing upon previous research implementing a longitudinal grounded theory design examining parental hope, 35 parents were interviewed regarding their experiences with an emergent description of the role of spirituality in parents' daily lives. Spirituality included religious beliefs and practices, notions of a higher force or cosmos, relationship with a divine being, as well as elements emerging from meaning-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 13 publications
3
45
0
11
Order By: Relevance
“…The studies defined spirituality through eight emerging themes identified through content analysis of direct quotes defining spirituality from each paper completed by the study team chaplain (KL) and content‐checked by the last author (MW): faith, meaning, religion, sense of the divine or a higher power, vitality and gratitude, spirituality, existential wellness, and hope. Seven studies defined spirituality in the context of faith, such as seeking healing, engaging in prayer, or participating in faith traditions . The overarching paradigm for defining spirituality focused on making meaning of the biomedical realities from diagnosis through prognosis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The studies defined spirituality through eight emerging themes identified through content analysis of direct quotes defining spirituality from each paper completed by the study team chaplain (KL) and content‐checked by the last author (MW): faith, meaning, religion, sense of the divine or a higher power, vitality and gratitude, spirituality, existential wellness, and hope. Seven studies defined spirituality in the context of faith, such as seeking healing, engaging in prayer, or participating in faith traditions . The overarching paradigm for defining spirituality focused on making meaning of the biomedical realities from diagnosis through prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies defined spirituality in the context of faith, such as seeking healing, engaging in prayer, or participating in faith traditions. 2,[32][33][34][35][36][37] The overarching paradigm for defining spirituality focused on making meaning of the biomedical realities from diagnosis through prognosis. The search for meaning included understanding illness, processing distress, and making sense of suffering.…”
Section: Definitions Of Spiritualitymentioning
confidence: 99%
See 3 more Smart Citations